A Design of Self Internal Entropy Balancing System with Incarnation Process - Shim, JeongYon (Bio-Inspired Computational Intelligence and Applications, 2007)
In this paper, adopting the concept of autonomic nervous system, we design Self Internal Entropy Balancing System with incarnation focused on the self maintaining function, we define self type and self internal entropy as a property of system. This system checks SEG(Surviving Energy Gauge) periodically and make a balance by adjusting the treatment. In the case of the situation to survive, it keeps the system by processing the incarnation process. It is applied to knowledge network system of virtual memory and tested with sample data.